Effect of Ser392 Phosphorylation on the Structure and Dynamics of the Polybasic Domain of ADP Ribosylation Factor Nucleotide Site Opener Protein: A Molecular Simulation Study - Srinivasaraghavan, Kannan (2016)
ADP ribosylation factor nucleotide site opener (ARNO) as a guanine nucleotide exchange factor (GEF) activates small GTPases called ADP ribosylation factors (Arfs), which function as molecular switches and regulate a variety of cell biological events. ARNO directly interacts with the transmembrane a2-subunit isoform of the proton-pumping vacuolar ATPase in an acidification-dependent manner, and this interaction plays a crucial role in the regulation of the protein degradation pathway. A recent study reported specific interactions of a2N with the ARNO375–400 peptide corresponding to the polybasic (PB) domain of ARNO, which is a crucial regulatory element in the autoregulation and modulation of Arf-GEF activity. Interestingly, phosphorylation of Ser392 completely abolishes this interaction, and the experimental structure shows significant structural rearrangements. To investigate the effect of Ser392 phosphorylation on the structure and dynamics of the ARNO375–400 peptide, we employed all atom molecular dynamics (MD) simulations of the phosphorylated and unphosphorylated PB domain of the ARNO protein. A Hamiltonian-based replica exchange method called biasing potential replica exchange MD was used to enhance conformational sampling. Simulations predicted that the isolated PB domain is highly flexible, with the C-terminal region of the unphosphorylated state being unstable. In contrast, Ser392 phosphorylation increases the overall stability of the peptide. In agreement with experimental results, our simulations further support the hypothesis that phosphorylation induces disorder to order transitions and provide new insights into the structural dynamics of the PB domain. Phosphorylation of Ser392 appears to stabilize the C-terminal α-helix via formation of salt bridges between phospho-Ser392 and Arg390, Lys395, and Lys396.